Tindak Tutur â€œRequestâ€ Bahasa Inggris dalam Metode Role Play pada Mahasiswa Keperawatan - Priyastuti, Maria Theresia (Journal of Language and Health, 2020)
This research discusses the form of request and the strategy of request in English learning process using role play method. Objective: to describe the form of request and the strategy of request in English learning process using role play method. Method: descriptive qualitative with equal pragmatic methods using theory of Edmondson and House and Aijmer. The data were taken from role play conversation which contained speech act of request. The total sampling were used 20 groups when the nursing students did role play of giving health education. Data methods used listening and direct observation (participatory observation). Results: firstly, speech acts of assertive request in English learning that often used in role play conversations are "you can .., you must (have to), you should ... you had better" and tentative requests for speech acts are "can you ...?, And would you ...? ". Secondly The speech act of the request strategy asserts that it is possible for the hearer to do something and asks for permission to do something. Conclusions: the form and the strategy of requests are found in English learning process using role play method.